Seleção de leveduras e produção de cerveja artesanal suplementada com selênio - Figueirêdo, Antonio Fábio Reis (2017)
The use of selected yeasts is an important aspect in the production of quality beers, since in addition to the production of ethanol and carbon dioxide they contribute significantly to the formation of secondary compounds, which confer the flavor of the beer. These yeasts also settle easily in the middle, avoiding undesired contaminations, in addition to generally presenting high rates of yield, productivity and fermentation efficiency. Selenium (Se) is a mineral that performs antioxidant functions, being essential as trace element to human health and its deficiency is correlated to the occurrence of several diseases. Due to these properties, the incorporation of Se into some food and / or food supplements associated with yeast is already a reality. Considering that beer is the most consumed alcoholic drink in the world, this research aimed to select yeasts to produce artisan beer supplemented with selenium. To do so, using the multivariate analysis technique, the selection of yeasts with potential for brewing was initially performed, and three strains (SC52, SC57 and SC82) were selected; Then applying the Doehlert factorial design and using the Response Surface Methodology technique, the optimization of the fermentation parameters (fermentation temperature and selenium concentration) for the production of beer supplemented with selenium was carried out. The yeasts SC52 and SC82 presented significant responses for the production of the supplemented beer, and the optimum values (Se concentration and fermentation temperature) were 11 mg L-1 and 25.0° C for yeast SC52 and 12 mg L-1 and 23.5° C for yeast SC82; (CSeSC52 and CSeSC82) were produced on a microbrewery scale, the fermentation parameters of the process were evaluated and total selenium and selenium species present in yeast and beers were quantified. The beers produced presented fermentative results within the commercial standards, being recommended by DDR (Recommended Daily Dose) of Se, a maximum consumption of approximately 600 mL of CSeSC52 beer and 740 mL of CSeSC82 beer.